(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The aim of the research is a techno-economic analysis of the use of concentrated solar energy technologies in the Iraqi city, considering the concentrated solar energy technology is a renewable energy technology that derives its resources from the sun and is replenished at a rate that exceeds its use. It is also inexhaustible and environmentally friendly energy from its environmental footprint, unlike traditional fossil energy which produces greenhouse gases and a major cause of global warming. This research measures the costs of concentrated solar energy technology to Reduce the effects caused by other energies and work to fill part of the shortfall in the total electricity production, even at a specific percentage, in preparation for spreading a culture of these clean technologies, and proposing investment in concentrated solar power (CSP) technology and choosing the best sites according to radiation rates. Direct solar radiation on which these technologies depend for their work. By comparing the cost between these clean technologies and traditional fossil techniques. In this research, the province of (Al-Anbar) was selected and the economic criteria for the construction of a concentrated solar power plant were studied. The study showed that the technology of concentrated solar energy has a direct impact on the cost of producing electrical energy and reduces the cost of producing kilowatt-hours by (9-11) cents the range to discount rate (5-7) and capacity factor ranged (40 %,45%) , regardless of the environmental problems produced by plants that operate on fossil fuels.